OPTIMIZING INVENTORY IN THE RECEIVING & STOREKEEPER DEPARTMENT OF A HOTEL USING THE MIN-MAX METHOD - Cahyaningrum, Nadia Wulandari; Kartini, Kartini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Inventory management plays a crucial role in hotel operations due to its direct impact on service continuity and cost control. Improper inventory management may result in excessive storage costs or operational disruptions caused by stock shortages. This study aims to analyze inventory optimization in the Receiving & Storekeeper department of a hotel using the Min–Max method. The research adopts a quantitative approach utilizing secondary data in the form of hotel inventory records. The analysis involves the calculation of safety stock, minimum stock, maximum stock, as well as inventory costs, including holding cost and ordering cost, accompanied by an inventory optimization index assessment. The results indicate that all analyzed inventory items are in optimal condition, as the actual stock levels remain within the established minimum and maximum limits. Furthermore, the total ordering cost exceeds the holding cost, reflecting a procurement pattern characterized by frequent orders with relatively small order quantities. These findings demonstrate that the Min–Max method is effective in maintaining inventory availability while controlling inventory-related costs, and can support more measured decision-making in hotel inventory management.